APPLICATION OF GOOGLE EARTH ENGINE IN FLOOD MONITORING AND ASSESSMENT OF FLOOD-AFFECTED AGRICULTURAL LAND IN THE BUI RIVER BASIN, HANOI CITY - Thu Ha, Tran; Ngoc Huan, Tran; Minh Tam, Phung; Thi Hai, Nguyen; Thi Cuc, Bui; Thanh Que, Pham; Dinh Tien, Nguyen; Hoai Nam, Ho (Journal of Forestry Science and Technology, 2023)
Tropical storms accompanied by heavy rain often appear and cause severe floods from May to November every year in the Bui river basin, seriously affecting the local agricultural production. Therefore, a quick assessment of the agricultural land area affected by inundation is very important for the people and local government officials. In this study, we propose a new method to quickly estimate the agricultural land area affected by floods using Sentinel 1A (S1A). Firstly, the flood map estimated from the S1A image on Google Earth Engine at the flood peak by the Otsu threshold method does not exclude permanent water area with an overall accuracy of 82,5%. The flood extent are estimated at 1324 hectares, approximately 4% higher than the official data of local authorities. Secondly, the study overlayed the official land map and the flood map to determine the location and area of the affected area by the flood. Calculation results show that storm Son Tinh has affected approximately 33% (1261 ha) of agricultural land ( not accounting forestry) in 5 communes. The difference is about 1.2 % (15 ha) compared with statistical results from state management agencies. The results show the valuable potential of using free Synthetic Aperture Radar (SAR) from S1A images to quickly monitor and assess flood-affected agricultural land over a small and large area using the Google Earth Engine.